PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA FISIK, DAN KOMPETENSI TERHADAP KEPUASAN KERJA KARYAWAN TETAP PT TELKOM AKSES KOTA BEKASI - Sultan Imran Hikam Fadillah (2022)
This research is a quantitative study that aims to determine the effect of leadership style, physical work environment, and competence on employee job satisfaction. The population in this study are all employees who work at PT Telkom Access Bekasi City area. The sample size was taken as many as 50 respondents, with a saturated sampling technique. Data was collected through the distribution of an online questionnaire in the form of a google form. The analytical technique used is the Partial Least Square (PLS) method through the SmartPLS 3 data processing application with a significance level of 5% (0.05). The results of this study indicate that (1) partially the work leadership style has a positive and significant effect on employee job satisfaction (2) partially the work environment has a positive and significant effect on employee job satisfaction (3) partially competence has a negative and significant effect on employee job satisfaction (4) simultaneously leadership style, physical work environment, and competence affect employee job satisfaction.